The chromodomain of LIKE HETEROCHROMATIN PROTEIN 1 is essential for H3K27me3 binding and function during Arabidopsis development. - Vivien Exner; Ernst Aichinger; Huan Shu; Thomas Wildhaber; Pietro Alfarano; Amedeo Caflisch; Wilhelm Gruissem; Claudia Köhler; Lars Hennig (PLoS ONE, 2009)
Polycomb group (PcG) proteins are essential to maintain gene expression patterns during development. Transcriptional repression by PcG proteins involves trimethylation of H3K27 (H3K27me3) by Polycomb Repressive Complex 2 (PRC2) in animals and plants. PRC1 binds to H3K27me3 and is required for transcriptional repression in animals, but in plants PRC1-like activities have remained elusive. One candidate protein that could be involved in PRC1-like functions in plants is LIKE HETEROCHROMATIN PROTEIN 1 (LHP1), because LHP1 associates with genes marked by H3K27me3 in vivo and has a chromodomain that binds H3K27me3 in vitro. Here, we show that disruption of the chromodomain of Arabidopsis thaliana LHP1 abolishes H3K27me3 recognition, releases gene silencing and causes similar phenotypic alterations as transcriptional lhp1 null mutants. Therefore, binding to H3K27me3 is essential for LHP1 protein function.